Readability of Risk Disclosure: An Analysis of Chinese Overseas Listing Companies - GAO, Wanwei (2008)
This dissertation examines the risk disclosures of annual reports by twelve Chinese overseas listing IT companies from the aspect of readability level of the texts. Using content analysis and readability formula (Flesch reading ease), the paper attempts to investigate how is the readability of sample companies risk disclosures, whether there are some correlations between readability and listing history, risk volume, firm size and profitability. In addition, this study also discusses the elements that may influence the readability level of risk reporting. The findings of this research are that there is no significant association between readability of risk disclosure and listing history, size, and profitability; that Flesch scores of each companys risk disclosure show a variance among risk categories; and that this variance may be correlated with disclosure volume of different risk factors.